Robot-assisted surgery for gynecological cancer - Hao Liang; Hang Yu; Jiangtao Fan (Intelligent Surgery)
With the advancements in technology and the progression of modern times, robotic surgical systems have emerged as a new trend in minimally invasive surgery and, have been applied to a variety of gynecological surgery. Robotic surgery has become a crucial treatment for gynecological cancer due to its unique advantages. This article outlines the history of minimally invasive surgery in common gynecological surgery, analyzes and summarizes the scope and current status of its application in gynecological tumor surgery. Based on the author's experience with thousands of robotic-assisted surgeries and the latest research progress, this article compares the learning curve and postoperative complications of robotic-assisted laparoscopic surgery versus traditional laparoscopic surgery. The strengths, weaknesses, and challenges faced by robotic-assisted systems in gynecological tumor surgery are also discussed. This comprehensive guidance provides valuable insights for young or novice gynecological oncologic surgeons in choosing appropriate surgical techniques for tumor procedures.